PREVALENCE OF SENSITIZATION TO AIRBORNE ALLERGENS IN PATIENTS WITH ALLERGIC RHINITIS AND ASTHMA IN UKRAINE - O.V. Mozyrskaya (Медична наука України, 2023)
Background. The distribution of sensitization among children and adolescence with allergic rhinitis (AR) and asthma and their impact on various allergic symptoms have been analyzed.